Pengembangan Bahan Ajar Matematika Berbasis Problem Based Learning Berbantuan Kvisoft Flipbook Maker Pro Di Sekolah Dasar - Hairani, Sunita; Amini, Risda (Universitas PGRI Madiun, 2023)
The research objective was to develop valid, practical, and effective integrated thematic teaching materials based on the PBL approach assisted by the Kvisoft Flipbook Maker Pro application in grade III elementary schools. This research is included in Research and Development research using the ADDIE development model. Collecting data using observation, interviews, questionnaires and written tests. Data analysis uses a Likert scale by looking at validation analysis, practicality, and effectiveness. The results obtained from the development of PBL-based integrated thematic teaching materials assisted by Kvisoft Flipbook Maker Pro in Class III Elementary Schools, namely the validity percentage of 89.06% (Content Validation), 80% (Graphical Validation), and 83.3% (Language Validation) . The practicality of the teacher's response was 80.00% (practical), while the student response was 80.26% (practical). Effectiveness is seen from student learning outcomes, namely the N-Gain Score of 0.71 (High) is obtained in the effective category. This means that the teaching materials developed are valid, practical, and effective for third grade elementary school students